PRINCIPLES AND METHODS OF TEACHING MATHEMATICS. INNOVATIVE EDUCATIONAL TOOLS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, the modern didactic principles of teaching mathematics, effective pedagogical methods, and the use of innovative educational tools are highlighted. It has been scientifically analyzed that applying key didactic principles— such as scientific approach, conscious activity, regularity, consistency, and visuality— directly affects the quality of mastering mathematics. In addition, the study examines the practical effectiveness of problem-based learning, the project approach, inquirybased teaching, and the competency-based approach alongside traditional methods. As innovative educational tools, the possibilities of digital platforms, online services, interactive simulators, artificial intelligence technologies, AR/VR systems, and electronic resources have been explored. The results show that the use of innovative methods and technologies in mathematics lessons significantly increases students’ logical thinking, creativity, and motivation. At the end of the article, methodological recommendations and suggestions are presented.